Agglomeration, Migration and Tax Competition - Kurt A. Hafner (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 2005)
This paper focuses on tax competition and international migration in R&D sectors as agglomeration forces and trade restrictions are present. Economic integration forces industrialized countries to adapt their tax rates in order to keep their industrial status quo. Unlike the often discussed "race to the bottom" result, taxes are increased and the provision of public goods is maintained. It is also proven that taxes that redistribute between mobile and immobile labor lead to a tax burden that favors mobile labor. As integration continues, the cutback of factor mobility restrictions supports economic development in industrialized countries at the expense of structurally backward regions.
Keywords: F22; R12; F12; H73; 330; Economic Geography; Agglomeration; Migration; Tax Competition; Steuerwettbewerb; Internationale Arbeitsmobilität; Mehr-Sektoren-Modell; Hochtechnologiesektor; Regionale Konzentration; Agglomerationseffekt; Optimale Besteuerung; Neue ökonomische Geographie; Theorie